Cutaneous vasculitis overlap with acute generalised exanthematous pustulosis (AGEP). (17th November 2014) - Murad, Aizuri; Murphy, Annette
Abstract : A man in his 40s developed a severe cutaneous adverse reaction following treatment of septic arthritis with flucloxacillin. The eruption had overlap features of cutaneous vasculitis and acute generalised exanthematous pustulosis which was complicated by renal and liver impairment. This case heightens the variation in presentation of a severe drug eruption.